Application of Authority Delegation to Improve Employee Performance in Family Companies of UD Sahabat - Chanif, Ahmad; Melinda, Tina (KnE Social Sciences, 2021)
Authority delegation is a process where managers allocate their authority to the subordinates who do the report for them. Authority delegation is a process of work distribution of company associates, so that they could work in accordance with their duties and be able to do the tasks effectively and efficiently. Authority delegation is executed as an effort to improve the performance of employees of a family company, UD Sahabat. The purpose of this study was to analyse the application of authority delegation in the company. This study used qualitative methods with descriptive techniques by collecting data through semi-structured interviews using the triangulation method of data sources. The participants in this study were four informants, which included company owners, company employees, professionals and HR experts. The results show that the company has 2 ways to apply delegation to its employees. First, directly: the owner of the company gives verbal authority and then instructs to immediately implement it and if there are some things that are not understood, the employee asks the company owner. Employees said that when they first worked for the company, they were only told to serve the buyers well; no special delegation was given. Second, indirectly: the delegation is given in writing and is usually applied to employees of the delivery of goods. Keywords: authority delegation, family company, employee performance